GENDER INTEGRATION IN THE MILITARY: GENDER-NEUTRAL STANDARDS AND COED SPORTS - Irene Kamberidou (European Journal of Physical Education and Sport Science, 2019)
This paper focuses on the socio-cultural aspects of gender integration in the Armed Forces, arguing for gender-neutral standards. It begins with a detailed literature review relevant to women’s integration in the military, subsequently focusing on Greece, and in the final analysis arguing that coed military sport participation and exercises serve as a means of bridging the gender-divide and eliminating gender harassment. Though coed sport (mixed-gender teams) as a tool for women’s inclusion and integration in the military seems to be part of the solution, it is a topic on which research is scarce (Kefi Chatzichamperi, 2018, 2019). This study does not examine physiologic attributes: biological and anatomical differences or research on sex hormones and how they affect the nervous system and physical strength, and subsequently soldier performance (Tenan, 2017). Using a qualitative theoretical approach, it discusses the social dimensions of evidence-based research on why and how gender integration is relevant. It includes current and ongoing studies presented at the 14th Conference of the European Research Group on Military and Society (ERGOMAS), hosted by the Hellenic Army Academy in Athens, indicating that a main challenge in the military today is to ensure a gender balance through women’s inclusion, active engagement and retention. Research emphasizes the need for change in the military culture on all levels—legal and organizational—including gender-awareness and diversity training, especially on the complimentary skills that both genders bring to the table as opposed to the "wastage of talent" (Kamberidou, 2013). Certainly, establishing gender-neutral standards to eliminate sexism, and promote inclusion and integration is a complex and multifaceted process, the reason researchers in the social sciences use a variety of theoretical approaches (Patsantaras, 2015, 2013; Seagrave, 2016). The results indicate that the gender participation gap continues in all current military organizations: Hungary holding the highest female participation rate (19.3%) and Turkey the lowest (0.8%).   Keywords: Degendering, gender/sex distinction, gender harassment, armed forces, homophobia, sexual and gender-based violence (SGBV), mixed-gender sports